Pemurnian dan Deteksi Serologi Patchouli Mottle Virus pada Tanaman Nilam - Sedyo Hartono; Siti Subandiyah; Aminatun Munawarti; Retno Mastuti; Serafinah Indriani (Universitas Gadjah Mada, 2006)
Patchouli mottle virus (PatMoV) is the most severe disease pathogen and causes substantial losses in many patchouli-producing regions in Indonesia. Serological detection tool for the disease was developed in this research. Virus isolation was conducted on Chenopodium amaraticolor resulted on the homogenous local lesions 6 days after inoculation. Virus purification was obtained from 200g inoculated leaves resulted on 2 ml virus solution with the concentration of 1 mg/ml. Polyclonal antibodies were produced on rabbits. Harvested antiserum was used for further virus detection by Indirect-Enzyme linked Immunosorbent assay (I-ELISA) and dot-immunobanding assay (DIBA) techniques. The antibodies were positively reacted with purified viruses, infected field collection of patchouli, and inoculated C. amaranticolor. On the other hand un-inoculated C. amaranticolor samples and healthy patchouli generated from tissue cultures gave negative reaction with the antibodies. This is the first report of cheap practical antibody production for PatMoV detection in Indonesia.